2023
DOI: 10.22495/jgrv12i3siart18
|View full text |Cite
|
Sign up to set email alerts
|

The token economy in a developing country

Ruangchan Thetlek,
Tanpat Kraiwanit,
Kris Jangjarat
et al.

Abstract: The token economy is a decentralized digital economy enabled by blockchain technology based on the premise of controlling asset ownership with digital tokens (Zhao et al., 2019). The increase in digital asset ownership among Thai residents over the past year (Kemp, 2022) is indicative of the expansion of the token economy. Therefore, the purpose of this study is to analyze the factors influencing the token economy in Thailand. Multiple regression analysis has been used to analyze the data acquired from Thai in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…This suggests that higher education levels were associated with a lesser impact of the Starlink project on the studied domains. The findings were in agreement with a study conducted Thetlek et al (2023), indicating that an individual's education level had a statistically significant positive relationship to the token economy. also confirmed that the effects of the Starlink project on the competitive structure of the Internet service provider market in Thailand can be described by education; it suggests that education level plays a significant role in determining how the project impacts competition among internet service providers in the country.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that higher education levels were associated with a lesser impact of the Starlink project on the studied domains. The findings were in agreement with a study conducted Thetlek et al (2023), indicating that an individual's education level had a statistically significant positive relationship to the token economy. also confirmed that the effects of the Starlink project on the competitive structure of the Internet service provider market in Thailand can be described by education; it suggests that education level plays a significant role in determining how the project impacts competition among internet service providers in the country.…”
Section: Discussionsupporting
confidence: 91%